PENGARUH BEBERAPA UKURAN DIAMETER PULLEY PADA PEMERAS SANTAN SISTEM SCREW PRESS (The Effect of Some Diameter Size Pulley of Screw Press Coconut Milk Extractor) - Chesya Ritonga; Achwil Putra Munir; Sulastri Panggabean (Universitas Sumatera Utara, 2018)
ABSTRACT The coconut milk extractor that had been designed previously was not effective in process, so the author suspect that the performance of the machine will be better if pulley with right diameters is used. The research’s purpose is to examine the effect of various pulley diameter on the effective capacity, yield, and the percentage of left material of the coconut milk extractor. This research was conducted in March 2017 to July 2017 in the Laboratory of Agricultural Engineering, Faculty of Agriculture, University of North Sumatra, using factorial randomized block design with one factor (2, 3, 4, 5 and 6). The parameters observed were effective capacity, yield and the percentage of left material on The coconut milk extractor. The result shows that the highest effective capacity was 34,75 kg/hour at treatment R5 with 6 inch pulley diameter, the highest yield was treatment R5 with 6 inch pulley diameter (77,75%), and the percentage of material left behind was the lowest at treatment of R5 with 6 inch pulley diameter (12%). From Duncan Multiple Range Tests it was found that the pulley diameter had highly significant effect on the effective capacity and had significant effect on percentage of material left behind and had no effect on yield. Keyword: coconut milk, effective capacity, yield and the percentage of left material, The coconut milk extractor ABSTRAK Alat pemeras santan sistem screw press yang telah dirancang sebelumnya dinilai kurang efektif dalam pengolahannya, sehingga penulis menduga akan terjadi perubahan kinerja alat apabila digunakan puli dengan diameter yang tepat. Penelitian ini bertujuan untuk menguji pengaruh berbagai diameter puli terhadap kapasitas efektif alat, rendemen, dan persentase bahan tertinggal pada alat pemeras santan sistem screw pres. Penelitian ini dilakukan pada bulan Maret 2017 hingga Juli 2017 di Laboratorium Keteknikan Pertanian, Fakultas Pertanian Universitas Sumatera Utara menggunakan rancangan acak lengkap non faktorial yaitu diameter puli (2, 3, 4, 5 dan 6). Parameter yang diamati yaitu kapasitas efektif alat, rendemen dan persentase bahan tertinggal. Dari hasil penelitian diperoleh kapasitas efektif alat tertinggi terdapat pada perlakuan R5 yaitu dengan diameter puli 6 inci sebesar 34,75 kg/jam, rendemen tertinggi terdapat pada perlakuan R5 yaitu dengan diameter puli 6 inci sebesar 77,75%, dan persentase bahan tertinggal yang terendah terdapat pada perlakuan R5 yaitu dengan diameter puli 6 inci sebesar 12%. Dari pengujian DMRT diperoleh bahwa diameter puli pada alat pemeras santan sistem screw press memberikan pengaruh berbeda sangat nyata terhadap kapasitas efektif alat dan memberikan pengaruh berbeda nyata terhadap persentase bahan tertinggal dialat dan memberikan pengaruh berbeda tidak nyata terhadap rendemen alat. Kata Kunci: santan kelapa, kapasitas efektif, rendemen dan persentase bahan tertinggal dialat, alat pemeras santan sistem screw press